PENGARUH PENGGUNAAN MEDIA BAAMBOOZLE PADA MATERI KEANEKARAGAMAN HAYATI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Fifth-grade elementary school students were given a Noble Character program; this study examined the obstacles and support for the program. This study adopted a qualitative approach with a descriptive case study design involving the coordinator of the Pancasila Student Profile Strengthening (P5) project, classroom teachers, and fifth-grade students at SD N 01 Pakisari. Data collection methods included observation, in-depth interviews, document analysis, and data analysis using data collection, presentation, and conclusion drawing strategies. The three main channels for implementing the Noble Character elements in fifth grade include intracurricular (integration into PAI and PPKn lessons), cocurricular (implementation of appropriate P5 projects, such as local policies or sustainable living), and school culture (daily activities such as tadarus, congregational prayers, and social activities). Although teacher consistency and the impact of the digital environment on student behavior are obstacles, parental support and school commitment play a major supporting role. This study concludes that comprehensive coordinated school strategies are essential to encourage the development of the Moral Values dimension.